UJI COBA MODEL LOYALITAS PELANGGAN DAN KELANGSUNGAN BISNIS MELALUI HUBUNGAN PELANGGAN PRODUKTIF, AKUNTABILITAS PRODUK DAN LAYANAN SIX SIGMA - Isnuwardiati, Kurnia; Sugito, Pudjo (University of Merdeka Malang, 2016)
This study intend to create adaptive solutions to the SME (Small and Medium Enterprises) in the outer circumference culinary Malang order to be sustainable. The reason is because so many problems faced by this business. Therefore, require a fast solution especially by maintaining customer loyalty. For that surely, need to look for a solution through empirical research. Further, the specific objectives of this study wanted to develop a new model to build customer loyalty and business sustainability through productive approach of customer relations, product accountability and governance-based Six Sigma (study of the development of SMEs in the area of ??culinary outer circumference of Malang). In this study, productive customer relationships, product accountability and governance-based Six Sigma as an exogenous variable, variable customer loyalty and business sustainability as an endogenous variable. First step, structural equation modeling analysis techniques used in the development and simultaneously test theoretical models. Second step, model tries out for selected small and medium industries. Based on the results of research conducted revealed that the productive customer relationships, product accountability and governance-based six sigma significant effect on customer loyalty and business sustainability. So that this result will be a new model in the culinary development of SMEs, particularly in the city of Malang and based on the trial results also reinforce these findings. It means the finding model of customer loyalty and competitiveness is really an adaptive model.